Development and Validation of a Performance Assessment Instrument for Lecturers in Higher Education - ., Mardainis; Giatman, Muhammad; ., Waskito; Andesa, Khusaeri (Journal of Ecohumanism, 2024)
Higher education plays a pivotal role in human resource development and national progress. Lecturers, as key contributors to the higher education system, significantly influence graduate quality through effective and efficient teaching practices. However, evaluating lecturers’ teaching performance comprehensively remains a challenge due to its multidimensional nature. Existing evaluation methods often rely on subjective assessments from students or peers, which are influenced by personal preferences and interpersonal relationships. Moreover, the instruments used frequently lack comprehensiveness, validation, and reliability, resulting in inaccurate evaluations. This study highlights critical issues in current evaluation practices, including reliance on single-source data, lack of transparency in feedback, uneven technological integration, and a focus on outcomes over teaching processes. These limitations hinder the utility of performance evaluations as tools for professional development, reducing their potential to enhance teaching quality. To address these challenges, this study proposes a comprehensive approach to lecturer performance evaluation, incorporating diverse perspectives—students, peers, self-assessments, and program heads—while emphasizing the need for validated instruments, technology integration, and constructive feedback mechanisms. By developing and implementing a robust and objective evaluation system, this research aims to support continuous professional development and improve teaching quality in higher education.